Swarm Intelligence Algorithms for Optimization Problems a Survey of Recent Advances and Applications - Mande Smita Samrat; M Srinivasulu; Anand Sruthi; K Anuradha; Tiwari Mohit; U Esakkiammal (ITM Web of Conferences)
For many years swarm intelligence (SI) algorithms have shown successful performance for complex optimization problems in many fields. Challenges are still there as computational complexity, premature convergence, sensitivity to parameters, and limitation of scaling in spite of their success. This creates a unique opportunity for SI algorithms to be further enhanced through these challenges. Parallelization and hybrid models can save a lot of computation resource consumption. Furthermore, moving past premature convergence provides more robust algorithms that can discover global optima. Moreover, the theoretical aspects of SI algorithms are still in their infancy and propose novel methods to improve predictability and reliability. The responsiveness of SI algorithms to parameter configurations facilitates the development of adaptive methods that dynamically adjust parameters, while the demand for a better exploration-exploitation balance creates opportunity for development of convergence strategies that improve efficiency. Moreover, achieving more sophisticated with the proposed constraints means that specific mechanisms could greatly improve the efficiency of multiple conditional tasks in the real world. As slow convergence and overfitting become noticeable obstacles, strategies for accelerated convergence and regularization techniques present opportunities for better and more generalized results. Finally, new designs in terms of scalability and memory efficiency will broaden the applicability of swarm intelligence algorithms in large-scale, resource-constrained environments. We present a survey of recent developments in SI algorithms, highlighting both their strengths and challenges, as well as potential new applications of these algorithms in optimization problems.